Reachable Set Bounding for a Class of Nonlinear Time-Varying Systems with Delay - Xingao Zhu; Yuangong Sun; Fanwei Meng (Advances in Mathematical Physics)
We investigate the problem of reachable set bounding for a class of continuous-time and discrete-time nonlinear time-varying systems with time-varying delay. Unlike some preceding works, the involved disturbance input and time-varying delay are not assumed to be bounded. By employing an approach which does not involve the conventional Lyapunov-Krasovskii functional, new conditions are proposed such that all the state trajectories of the system converge asymptotically within a ball. Two illustrative examples are also given to show the effectiveness of the obtained results.